Effect of Rebonding on the Bond Strength of Orthodontic Tubes: A Comparison of Light Cure Adhesive and Resin-Modified Glass Ionomer Cement In Vitro - Monika Aleksiejunaite; Antanas Sidlauskas; Arunas Vasiliauskas (Hindawi Limited, 2017)
The purpose of this study was to determine the impact of different enamel preparation procedures and compare light cure composite (LCC) and resin-modified glass ionomer (RMGI) on the bond strength of orthodontic metal tubes rebonded to the enamel. Twenty human molars were divided into two groups (n=10). Tubes were bonded using LCC (Transbond XT) in group 1 and RMGI (Fuji Ortho LC) in group 2. The tubes in each group were bonded following manufacturers' instructions (experiment I) and then debonded using testing machine. Then, the same brackets were sandblasted and rebonded twice. Before the first rebonding, the enamel was cleaned using carbide bur (experiment II) and before second rebonding, it was cleaned using carbide bur and soda blasted (experiment III). Mann-Whitney and Wilcoxon signed-rank tests showed no significant difference between RMGI and LCC bond strengths in case of normal bonding and rebonding, when enamel was cleaned using carbide bur before rebonding. Enamel soda blasting before rebonding significantly increased RMGI tensile bond strength value compared to LLC (p<0.05). LCC and RMGI (especially RMGI) provide sufficient bond strengths for rebonding of molar tubes, when residual adhesive from previous bonding is removed and enamel soda blasted.